Current Progress on Host Antiviral Factor IFITMs - Ren, Linzhu; Du, Shouwen; Xu, Wang; Li, Tiyuan; Wu, Shipin; Jin, Ningyi; Li, Chang (Frontiers in Immunology, 2020)
Host antiviral factor IFITMs (interferon-induced transmembrane proteins) is a kind of small-molecule transmembrane proteins induced by interferon. Its broad-spectrum antiviral activity and unique ability to inhibit viral invasion have become a hot molecule in antiviral research in recent years. Since the first demonstration of its natural ability to resist viral infection in 1996, IFITMs have been reported limiting a variety of viral infections, including some major pathogens that seriously endanger human health and social stability, such as influenza A virus, Ebola virus, severe acute respiratory syndrome virus, AIDS virus, Zika virus, etc. Studies have shown that IFITMs mainly exerts antiviral activity during the virus entry, specifically interfering with the fusion of the envelope and the endosome membrane or forming fusion micropores to block the virus from entering the cytoplasm. However, its specific mechanism is still unclear. This article mainly reviews the research progress in the structure, evolution, function, and mechanism of IFITMs, which may provide a theoretical basis for clarifying the molecular mechanism of interaction between the molecule and viruses, and the research and development of new antiviral drugs based on IFITM.